2000
DOI: 10.3171/jns.2000.92.3.0390
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin concentrations after aneurysmal subarachnoid hemorrhage

Abstract: Endothelin concentrations seem to correlate with delayed cerebral ischemia and vasospasm after SAH. The highest levels of ET are predictive of the symptoms of cerebral ischemia and vasospasm, and ET may also worsen ischemia in patients with a history of hypertension. Thus, ET may be an important causal or contributing factor to vasospasm, but its significance in the pathogenesis of vasospasm remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
6

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 76 publications
(176 reference statements)
6
63
0
6
Order By: Relevance
“…Our observation that subjects with evidence of severe vasospasms (higher CBFV) exhibit higher ET-1 concentrations in CSF is in accordance with some [5][6][7][8][9]35 but not all 9 earlier studies that reported possible associations between ET-1 levels and cerebrovascular complications. It must be noted that ET-1 may also act in a paracrine fashion 36 ; therefore, a strong correlation between ET-1 concentration and vasospasm is not mandatory to establish the pathogenetic importance of ET-1 in SAH.…”
Section: Faßbender Et Al Et-1 In Subarachnoid Hemorrhage 2973supporting
confidence: 78%
See 2 more Smart Citations
“…Our observation that subjects with evidence of severe vasospasms (higher CBFV) exhibit higher ET-1 concentrations in CSF is in accordance with some [5][6][7][8][9]35 but not all 9 earlier studies that reported possible associations between ET-1 levels and cerebrovascular complications. It must be noted that ET-1 may also act in a paracrine fashion 36 ; therefore, a strong correlation between ET-1 concentration and vasospasm is not mandatory to establish the pathogenetic importance of ET-1 in SAH.…”
Section: Faßbender Et Al Et-1 In Subarachnoid Hemorrhage 2973supporting
confidence: 78%
“…29 -32. We also detected ET-1 in peripheral blood in the range of concentrations previously reported. 9 Systemic stress response could explain the release of ET-1 in the systemic circulation. Because levels in CSF were similar or even more elevated than in peripheral blood in many patients, ET-1 detected in CSF was unlikely to be derived only from the systemic circulation.…”
Section: Faßbender Et Al Et-1 In Subarachnoid Hemorrhage 2973mentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelin (ET) levels increase after SAH (23,35), and the acute fall in cerebral blood flow after SAH in rats is attenuated by inhibitors of the synthesis of ET or ET receptor blockers (9). Enhanced turnover of fatty acids and increased formation of vasoconstrictor metabolites of arachidonic acid (AA) have also been observed after SAH (10,12).…”
mentioning
confidence: 99%
“…De las tres isoformas conocidas, la ET-1 y la ET-3 han sido involucradas en la patofisiología del VC inducido por HSA. Aunque se han descrito algunas discrepancias, se reconoce que los pacientes que han sufrido una HSA tienen niveles altos de ET-1 y ET-3 en LCR y plasma 12,36,74 . Algunos autores han basado la polémica de la ET en el VC en que ésta también es producida por los astrocitos y en el hecho de que no siempre se ha encontrado una correlación clínica en pacientes con VC 25, 58 .…”
Section: Bloqueo De Espasmógenos: Antagonistas De Receptores Tipo a Dunclassified